Algebra II-Please check my solution
posted by Joella .
Solve by elimination method-thanks fro checking my work
2x + 3y= 2 multiply this equation by 2= 4x + 6y = 4
4x-2y = -28
4x + 6y = 4
-4x -2y = -28
8y = 32
y = 4
2x + 3(4) = 2
2x + 12 = 2
2x + 2-12
2x = -10
x = -5
solution = (-5,4)
you're on the right track but when you tried to subtract the 2 eq you only subtracted the first term, but left the others' signs the same.
It should look like this:
-4x+2y=28 now add the two eq together and redo the work you did before. if you have more questions just ask!
when I wrote the -4x -2y = 28
I forgot to put the next step which was -4x + 2y = 28
but isn't the rest of my steps the same still because when I subtracted those they became 8y = 32 and the rest Thanks for responding-I'm not sure if this isn't right still-I think the answer is correct minus the one step I forgot to write
I think I see where you mistook what I wrote-I'm doing the elimination method and subtracting the equations so the new equations were
4x + 6y = 4 after I multiplied first equation by 2
minus 4x -2y = -28 and so the 4x becomes -, the -2y becomes positive and the -28 becomes positive, correct
You're right. I'm sorry. When I saw the missed step, I stopped looking at the rest of the work. You are correct.